Four‐year entecavir therapy reduces hepatocellular carcinoma, cirrhotic events and mortality in chronic hepatitis B patients. (4th October 2016) - Su, Tung‐Hung; Hu, Tsung‐Hui; Chen, Chi‐Yi; Huang, Yi‐Hsiang; Chuang, Wan‐Long; Lin, Chun‐Che; Wang, Chia‐Chi; Su, Wei‐Wen; Chen, Ming‐Yao; Peng, Cheng‐Yuan; Chien, Rong‐Nan; Huang, Yi‐Wen; et al.
Abstract: Background & Aims: Oral antiviral therapy may reduce the disease progression of chronic hepatitis B (CHB) patients. We aimed to further investigate the efficacy of long‐term entecavir therapy in reduction of the risk of hepatocellular carcinoma (HCC), cirrhotic events and mortality in a large group of CHB‐related cirrhosis patients. Methods: The C‐TEAM (Cirrhosis‐Taiwanese EntecAvir Multicenter) study was a nationwide, multicenter, retrospective–prospective cohort study in Taiwan. We enrolled treatment‐naïve patients with CHB‐related cirrhosis and baseline HBV‐DNA≥2000 IU/mL receiving long‐term entecavir therapy and compared the development of HCC, cirrhotic events and mortality with that of a historical untreated cohort. Results: In total, 1315 entecavir‐treated and 503 untreated patients with cirrhosis were enrolled, with median treatment and follow‐up durations of 4 and 6 years respectively. Compared with the untreated cohort, entecavir therapy was associated with a 60% HCC risk reduction [hazard ratio (HR): 0.40, 95% confidence interval (CI): 0.28‐0.57]. Additionally, an older age, the male gender, HBeAg positivity, alpha‐fetoprotein (AFP)≥7 ng/mL before therapy were independent predictors of HCC development. Further analysis showed that entecavir therapy significantly reduced risks of variceal bleeding, spontaneous bacterial peritonitis, and liver‐related and all‐cause mortality. These findings were confirmed by propensity score‐matched cohorts in sensitivity analysis. In patients under entecavir therapy, an older age, the male gender, HBeAg positivity, AFP level ≥7 ng/mL before therapy, and 1‐year virological response were predictive of HCC development. Conclusions: Four‐year entecavir therapy significantly reduces the risk of HCC, cirrhotic events and mortality in patients with CHB‐related cirrhosis. Abstract : See Editorial on Page1752